2015
DOI: 10.3109/00016357.2014.939709
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of premature loss of primary teeth and its impact on malocclusion in the Eastern Province of Saudi Arabia

Abstract: A high prevalence of premature loss of teeth was found in this study. This finding emphasizes the importance of increasing awareness levels about this issue and focuses attention on the need for more preventive efforts to maintain healthy and normal dentitions that would improve the masticatory function and aesthetics of individuals and the whole population. In addition, the findings emphasize the importance of the early detection of premature loss of primary teeth to prevent future malocclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 5 publications
4
31
2
3
Order By: Relevance
“…The prevalence of loss of primary teeth has been studied only rarely. However, studies carried out of Mexico reveal prevalence ranging from 8.5–51.0% 3 5 6 ; the prevalence in this study was 24.7%. Preserving primary teeth until normal exfoliation is one of the most important factors in preventive and interceptive dentistry.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The prevalence of loss of primary teeth has been studied only rarely. However, studies carried out of Mexico reveal prevalence ranging from 8.5–51.0% 3 5 6 ; the prevalence in this study was 24.7%. Preserving primary teeth until normal exfoliation is one of the most important factors in preventive and interceptive dentistry.…”
Section: Discussioncontrasting
confidence: 52%
“…In this sense, dental extraction is the most common form of dental treatment in developing countries despite the significant progress made in recent years in dentistry 4 . The results of studies realized in various countries have reported prevalence of premature loss of primary teeth ranging from 8.5% in Venezuela 3 to 16.5% in India 5 to 51% in Saudi Arabia 6 .…”
mentioning
confidence: 99%
“…When posterior teeth move frontally, they cause secondary crowding of teeth erupting later, and the unilateral loss of a front tooth can cause disruption of the midline of the incisors resulting from the shift of the adjacent teeth to the free space [9]. Al-Shahrani, et al [10] found among boys who prematurely lost their milk teeth higher incidence of right-sided Angle's Class II, left-sided Angle's Class II (p=0.062), right-sided Angle's Class III, left-sided Angle's Class III (p=0.062), bilateral cross bite and abnormal overjet. Premature loss of deciduous teeth is still too frequent, which was confirmed by Grippaudo et al [11] in their studies conducted among 3017 children -in 14.6% of the children there was premature loss of deciduous teeth.…”
Section: Discussionmentioning
confidence: 99%
“…An attempt to demonstrate the negative impacts of ECC have been made in various ways. Objective parameters, such as a child's body weight and height, restricted growth, and future dentition problems, have been shown as evidence of the impact [2][3][4][5][6]. However, these little in uence on encouraging preventive practices in the groups affected by ECC or at risk for it.…”
Section: Introductionmentioning
confidence: 99%